1996
DOI: 10.1366/0003702963906203
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Studies of Metal-Humic Complexes with the Use of Lanthanide Ion Probe Spectroscopy

Abstract: The acidic functional groups of humic materials are an abundant source of metal binding sites in the natural environment. Studies of metal binding to humics are of great environmental interest because the biological and physicochemical properties of metals are often changed dramatically as a result of complexation with humics. In order to understand how these heterogeneous organic macromolecules bind metals with such a large range of binding energies, lanthanide ion probe spectroscopy (LIPS) has been used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…This technique has been used to study the Ln(III)/HS interactions, and the rationale was to either determine interaction constants [37,39,40], or gather information on the Ln/An(III) chemical environment [26,[41][42][43][44][45][46][47][48]. The observed luminescence corresponds to the 5 D 0 → 7 F 0 transition (electric and magnetic dipole forbidden, maximum around 580 nm), the 5 D 0 → 7 F 1 transition (magnetic dipole, maximum around 593 nm), and the 5 D 0 → 7 F 2 'hypersensitive' transition (electric dipole, maximum around 615 nm).…”
Section: Time-resolved Luminescence Spectroscopymentioning
confidence: 99%
“…This technique has been used to study the Ln(III)/HS interactions, and the rationale was to either determine interaction constants [37,39,40], or gather information on the Ln/An(III) chemical environment [26,[41][42][43][44][45][46][47][48]. The observed luminescence corresponds to the 5 D 0 → 7 F 0 transition (electric and magnetic dipole forbidden, maximum around 580 nm), the 5 D 0 → 7 F 1 transition (magnetic dipole, maximum around 593 nm), and the 5 D 0 → 7 F 2 'hypersensitive' transition (electric dipole, maximum around 615 nm).…”
Section: Time-resolved Luminescence Spectroscopymentioning
confidence: 99%
“…On the other hand, a study using the fluorescence lifetime of Eu 3+ reported that Eu 3+ -HS complexation (mixture of SRHA and SRFA) at pH 3.5 and at a lower REE loading level (10 -2 -10 -7 M Eu 3+ , 30 mg/dm 3 HS) is dominated by tetradentate complexes (Thomason et al, 1996). According to the study, a decrease in the REE loading level leads to an increase in the denticity of HS to Eu 3+ .…”
Section: Relationship Between Slope Of Ree Pattern Of Logk and Denticitymentioning
confidence: 99%
“…Poly-dentate metal coordination is therefore possible within one SRFA molecule or among SRFA molecules. A study using lanthanide ion probe spectroscopy (LIPS) found that Eu 3+ complexation by Suwannee river DOM (mixture of HA and FA) at pH 3.5 is dominated by tetra-dentate complexes at low metal to ligands ratios (100 nM Eu 3+ , 30 mg L À1 DOM) (Thomason et al, 1996). The LIPS study also indicated that an increase in metal/DOM ratio resulted in progressively less chelated complexes, with a gradual succession from 4 to 3 to 2 to 1 carboxyl groups bound to Eu 3+ .…”
Section: Comparison Of K Clnhs To Literature Datamentioning
confidence: 99%